2020
DOI: 10.1021/acsanm.0c02694
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Light-Management Interfaces by Polyol-Synthesized Silver Nanoparticles for Industrial Scale Silicon Solar Cells

Abstract: Plasmonic interfaces are used as an alternative and highly effective light management technique for solar cells. Topdown approaches produce well-ordered and carefully designed plasmonic structures for tailor-made light management; however, they are costly, and their fabrication is time-consuming. Thus, their utilization for industrial-scale solar cells is not trivial. It has been shown that dewetting is a cost-and time-effective bottom-up approach for the fabrication of plasmonic interfaces, yet it lacks preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…40 The solar cell with silver nano-cylinder or nano-cube pattern achieved a 6% enhancement in efficiency when considering a 170-µm-thick silicon wafer. 62 In our design, it is shown that a three-layer NW can achieve 17.58% PCE, one of the highest values so far reported for such a thin solar cell, with a total height of only 268 nm. This trend is a strong validation of our 2NWs and 3NWs ARC designs based on the results obtained from both optical and electrical simulations.…”
Section: Electrical Simulation Results and Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…40 The solar cell with silver nano-cylinder or nano-cube pattern achieved a 6% enhancement in efficiency when considering a 170-µm-thick silicon wafer. 62 In our design, it is shown that a three-layer NW can achieve 17.58% PCE, one of the highest values so far reported for such a thin solar cell, with a total height of only 268 nm. This trend is a strong validation of our 2NWs and 3NWs ARC designs based on the results obtained from both optical and electrical simulations.…”
Section: Electrical Simulation Results and Discussionmentioning
confidence: 62%
“…A moth eye‐inspired texturing pattern yields a PCE value of only 9.76% when considering a 700‐nm‐thick pattern on top of a 10‐µm‐thick silicon wafer with a back reflector 40 . The solar cell with silver nano‐cylinder or nano‐cube pattern achieved a 6% enhancement in efficiency when considering a 170‐µm‐thick silicon wafer 62 . In our design, it is shown that a three‐layer NW can achieve 17.58% PCE, one of the highest values so far reported for such a thin solar cell, with a total height of only 268 nm.…”
Section: Electrical Simulation Results and Discussionmentioning
confidence: 99%
“…(i) Versatility: Polyol synthesis of the nanoparticles is renowned for its versatility, primarily attributed to its ability to accommodate a wide range of materials, sizes and shapes [89][90][91]. This method is applicable to diverse nanoparticles, encompassing noble metals, metal oxides and even bimetallic alloys.…”
Section: F Synthesis Of Nanocompositesmentioning
confidence: 99%